FORMATION OF STUDENTS’ SCIENTIFIC THINKING BASED ON THE LEARNING OF METHODS OF THE SUBSTANCE ANALYSIS - M. A. Kosareva; L. A. Baikova; E. A. Nikonenko; V. V. Vaitner; A. N. Gabdullin (Образование и наука)
Introduction. In Federal State Standards of the Higher Education (FSS HE) of the natural-science and technical specialties and also in a number of the corresponding professional standards, the competence in the field of analytical chemistry is specified as one of the main qualification characteristics of an expert/university graduate. It is caused by interdisciplinarity of analytical chemistry and a wide range of application of analysis methods which are used today not only directly on chemical production, but also in power engineering, construction engineering, metallurgy, materials science, standardization, certification, and many other spheres. At the current time, however, there is a big gap between achievements of chemical science and content of high school discipline that reduces quality of staff training demanded in labour market. This discrepancy is caused both by preservation of traditional methodology of teaching chemistry and the reasons of the methodical plan. The aim of the publication is to search for more effective and productive ways of mastering the educational material that is relevant for acquiring the qualifications required from the university graduate. Methodology and research methods. Methodological framework of the article involves the concepts of chemical and natural-science education at the higher school; the principles of the system-based, cognitive, practice-focused and competence-based training. Results and scientific novelty. On the basis of the review and generalization of scientific and methodological resources on the theory and practice of application of the analysis methods of substances from didactic positions, a number of these methods have been singled out and compared; their role and features in determination of a molecule structure and other characteristics of an individual substance and its solutions have been shown. Despite the fact that the work is carried out using known methods of analysis, such a generalization makes it possible to more clearly understand the principles of the choice of a method and the method importance according to the purposes and specifics of the studied object that is essential for formation of research skills during training, as well as for formation of scientific thinking and the required qualification acquisition by graduates of the natural-science and technical specialties. In order to update the acquired knowledge, the examples illustrating applied use of various analysis methods in modern research and production practice have been collected. Tables have been made for a faster perception of the material by methods of analysis for the purpose of an informed choice of the method. Reliance on the principle of tabular collection of material makes it easier to understand the individuality of the method; allows teachers to reduce their workload; and on the part of students, to shorten the time and simplify the procedure of choosing the method of chemical, physicochemical and/or physical analysis. Practical significance. The work is compiled in accordance with the State General Educational Standards of Higher Professional Education, and can be recommended to practising and beginning teachers of higher education institutions, as well as graduate students of chemical specialties. The materials presented in the article can assist in designing the curricula of chemical disciplines or modules of educational programs.